(untitled) (Revista Brasileira de Ensino de Ciências e Matemática, 2020)
Knowledge was always a powerful strategy, orienting the development of societies, economies, cultures and individuals. The analysis of the science history reveals its most relevant tonic: the logical-experimental posture, responsible for all the most recent and important technologies for the eurocentric history. However, undeniable authority of scientific knowledge betrays its own origins when it kills the self-criticism, a heritage that comes from universal science, absolute and unchangeable. In this scenario, the teach of Science, carries the aspects that surrounds its own scientific history. The complaints of Basic Education students, that learning Science means “memorize dificult words”, are not rare. On that manner, this research has as an objective the proposal of an investigative activity, by the interchange between academy and school, aiming for science popularization. The methodological path occurred in a qualitative research, based on an exploratory studying, with the proposition of pedagogical intervention. It was developed a sequence of investigation study (SEI) with 70 students of a public High School. The SEI used was oriented by three key-steps predicted by Carvalho (2013): questioning; systematic and contextualization of knowledge. Through the proposed study, it was imposed that the investigative teaching, as a pedagogical approach, amplified the scientific repertoire of the participating students and of its method, through which they could test and found out the negative influence of saline environment on the development of vegetables. In this sense, we advocated a proposal of trialetical teaching, based on the mixed between: investigating, litiracy and scientific education, essential conditions to the popularization of science and entering in the intensive knowledge society.